Analisis Pencantuman Nama Perwakilan Diplomatik Asing dalam Exit Control List Pakistan terhadap Perlindungan Hak-Hak Kekebalan Diplomatik: (Studi Kasus Kolonel Hall di Islamabad) - Tasya Ester Loijens (CV Rewang Rencang, 2021)
A diplomatic representative is a person who carries the task of officially connecting the tongues of two countries, namely between the sending country and the receiving country. As a representation of a country, diplomatic representatives are given the privilege of immunity to be able to perform the duties and missions charged to it. Such privilege arrangements are legally regulated under the Vienna Convention of 1961 and supported by other sources of international law including international customary law. However, there are some obstacles in its application such as in the case of Colonel Hall in Islamabad, Pakistan. The accident caused by Colonel Hall's negligence in violation of traffic markings has left the victim dead and seriously injured. However, due to legal immunity, the authorities have not yet completed an investigation into the case. The Pakistani government then listed Colonel Hall's name on the Blacklist and recommended putting his name on the Exit Control List. How the incident is reviewed from the perspective of international law will be discussed by the author in this paper.